Scoping review of precision child and youth mental health research: dwelling in possibility - Lyeo, Joonsoo Sean; Blais, Angelica; Cloutier, Paula; Boafo, Addo; Dargél, Aroldo; Helleman, Amanda; Tanya, Tanya; Kashala-Abotnes, Esperance; Honeywell, Christina; Pajer, Kathleen (Frontiers in Psychiatry, 2026)
IntroductionPrecision child and youth mental health (PCYMH) offers a promising array of tools and methodologies to address the intensifying burden of mental health challenges in child and youth populations. However, the current state of PCYMH research requires better characterization. To this end, we conducted a scoping review aiming to provide a ‘lay of the literature’ for this emerging field.MethodsFollowing the Joanna Briggs Institute methodology for scoping reviews, we searched PubMed and Embase for PCYMH studies from January 1, 1980 to November 30, 2023, updating the search on November 1, 2024. The final dataset comprised 124 publications, summarized with descriptive quantitative analysis and qualitative content analysis.ResultsQuantitative analyses revealed that 48% (60/124) of studies had been published between 2020 and 2024, with the majority (51% (63/124)) studying populations in the U.S. Most studies were observational in design. Content analysis revealed four categories of PCYMH research focus: (1) Biomarkers (68% (84/124)); (2) Non-Biological Markers (17% (22/124)); (3) Implementation of PCYMH Interventions (14% (17/124)); and (4) Predictive Algorithms (5% (6/124)). PCYMH tools were underutilized and infrequently combined. Studies producing multimodal profiles of participants, e.g., using neuroimaging, genetics, digital health data, and lifestyle data were scarce. No study used reporting guidelines.DiscussionOur findings indicate that this body of research is still in its infancy. We highlight opportunities to advance the study of PCYMH and provide recommendations to support the maturation of this new field.